Development of an effective in vitro Regeneration protocol for BARI Mash 2 (Vigna mungo L.) an important legume crop in Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2017)
Black Gram (Vigna mungo L.), widely known as Mashkalai in Bangladesh is an important protein source used as human food as well as fodder. BARI Mash 2 is a popular black gram variety released by Bangladesh Agriculture Research Institute (BARI) which is cultivated throughout the country and very popular especially in the char areas. Establishment of a reliable regeneration system for BARI Mash 2 has been tried for further genetic improvement. A rapid, reproducible and efficient in vitro regeneration method was developed using hypocotyl and young leaf explants through callus formation. The frequency of callus formation was highest (75%) on Murashige and Skoog (MS) medium supplemented with a high concentration (31.66 ?M) of 2,4-Dichlorophenoxyacetic Acid (2,4-D) using the young leaf as explants source. Callus induction rate was less in hypocotyls in the same medium. No further progress was observed from those calluses. MS medium containing 16.11?M of ?- Naphthalene acetic acid (NAA) showed the 70% calli induction from hypocotyls segment. These calli were amenable to produce multiple shoots (5-6 shoot) in the medium containing 17.75 ?M of 6 Benzyl aminopurine (BAP) alone and the combination of BAP (17.75 ?M ) and NAA (2.68 ?M). Shoots were rooted most effectively (55%) in half strength MS basal medium containing 7.38 ?M of Indole-butyric Acid (IBA). Well rooted plantlets were successfully acclimatized, transferred to the soil and found to produce flowers and fruits. The efficient and reproducible regeneration protocol described here allows for successful in vitro regeneration of BARI Mash 2 that is vital for future genetic manipulation.Jahangirnagar University J. Biol. Sci. 6(1): 23-33, 2017 (June)